Towards competitive UMKM: Capacity building program in North Sulawesi - Ade Yusupa; Victor Tarigan; Jimmy Reagen Robot (Community Empowerment, 2024)
APIK North Sulawesi MSME members, particularly in Manado City, face challenges in accessing quality raw materials, production technology, and effective management knowledge. To address these issues, this community service program aimed to enhance the capacity and competitiveness of MSMEs through intensive training in NIB registration, digital marketing using Google Business, and graphic design with Canva. The program successfully increased participants’ understanding and skills, with 67.5% completing all training modules. MSMEs improved business legality through NIB registration, enhanced online visibility via Google Business, and created more appealing promotional materials. Ongoing mentoring contributed to increased sales and overall business performance. This program significantly addressed APIK MSME challenges and stimulated local economic growth.